Monitoring Linear Accelerator Output Constancy and Overall Performance Using the PTW Quickcheckwebline - Nyaichyai, K. S.; Jha, D.; Adhikari, K. P.; Prajapati, R.; Neupane, R. (Journal of Nepal Physical Society, 2022)
Daily morning quality assurance (QA) for all available beams using conventional phantom measures only output and beam quality. PTW QUICKCHECKwebline (PTW QCw) is a compact movable light-weight dosimetry equipment used for daily QA, capable of measuring flatness, symmetry, beam quality and output constancy of a given beam in a single exposure. The purpose of this study was to analyze and monitor the output constancy of a medical linear accelerator using PTW QCw and assess the overall performance of the PTW QCw. The output parameters of 4, 6 and 15 MV photon beams and 4, 6, 8, 10, 12 and 15 MeV electron beams of the Elekta Synergy linear accelerator in Kathmandu Cancer Center were analyzed. It was found in the study that all the parameters were well within the recommended tolerance limit of ±3%. Some known modifications in the settings of the linear accelerator gantry, couch, and collimator were introduced separately during the exposures, and the percentage variations from the baseline values were noted to check the sensitivity of the PTW QCw using 6 MV photon beam. The PTW QCw was able to detect the deviations introduced to the external irradiation conditions for both photon and electron beams under daily testing conditions. The results from this study suggest that daily dosimetric consistency measurements using the PTW QCw helps to monitor the overall performance of the linear accelerator.